2011
DOI: 10.2139/ssrn.1865171
|View full text |Cite
|
Sign up to set email alerts
|

Smart Meter Devices and the Effect of Feedback on Residential Electricity Consumption: Evidence from a Natural Experiment in Northern Ireland

Abstract: SummaryUsing a unique set of data and exploiting a large-scale natural experiment, we estimate the effect of real-time usage information on residential electricity consumption in Northern Ireland. Starting in April 2002, the utility replaced prepayment meters with "smart" meters that allow the consumer to track usage in real-time. We rely on this event, account for the endogeneity of price and plan with consumption through a plan selection correction term, and find that the provision of information is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 9 publications
1
58
0
2
Order By: Relevance
“…Gans et al. (), Ivanov et al. (), and Jessoe and Rapson () find that different technologies including smart meters and smart thermostats are associated with energy savings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gans et al. (), Ivanov et al. (), and Jessoe and Rapson () find that different technologies including smart meters and smart thermostats are associated with energy savings.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has documented that consumer responsiveness to TOU prices is impacted by different types of enabling technologies (Allcott, 2011a;Jessoe & Rapson, 2014). Gans et al (2013), Ivanov et al (2013), and Jessoe and Rapson (2014) find that different technologies including smart meters and smart thermostats are 4 A number of dynamic pricing experiments were conducted in the late 1970s and early 1980s, as a result of the energy crisis during the 1970s. Some of the conclusions of these pilot programs are summarized in Aigner (1985).…”
Section: Introductionmentioning
confidence: 99%
“…Faruqui, et al (2010) concluded that the average reduction in energy use was 7%, without accounting for the impact of time-dependent tariffs. Similarly, Gans et al (2013) found that energy use in Ireland dropped between 11 and 17% when smart meters replaced old meters in a natural experiment. Houde et al (2013) collaborated with Google in an experiment in which over 1,500 Google employees participated voluntarily.…”
Section: Smart Metersmentioning
confidence: 92%
“…Feedback on energy consumption is possible directly or indirectly. A large-scale experiment in Northern Ireland [16] with keypad meters shows savings in electricity consumption of 15% to 20%. Keypad meters provide consumption information and costs on an interactive display and customers may add credit to their card for example online.…”
Section: Feedback Made Possible By Smart Metering Devicesmentioning
confidence: 99%